THU0122 THE LACK OF EXERCISE HABIT WAS A RISK FACTOR FOR CLINICAL FRACTURES IN PATIENTS WITH RHEUMATOID ARTHRITIS -TOMORROW STUDY-. (June 2019) - Anno, Shohei; Inui, Kentaro; Sugioka, Yuko; Mamoto, Kenji; Okano, Tadashi; Tada, Masahiro; Koike, Tatsuya; Nakamura, Hiroaki
Abstract : Background: Patients with rheumatoid arthritis (RA) might be considered to be at increased risk of falls and fractures. However, little is known about the exact properties of risk factors for clinical fractures in patients with RA. Recently, the disease activity of RA has been more satisfactorily controlled by the ''treat-to-target" strategy, including the use of biologics. Given this new era, it is important to accurately estimate the incidence of clinical fracture in patients with RA and to elucidate contributing risk factors. Objectives: The objective of this study was to evaluate the incidence of clinical fractures and associated risk factors in 208 patients with RA and in age- and sex-matched 205 controls (Cont) who participated in the TOMORROW (TO tal M anagement O f R isk factors in R heumatoid arthritis patients to lOW er morbidity and mortality) study, a 10-year cohort study that started in 2010 in Japan. This research was conducted using TOMORROW study data for 7 years. Methods: We evaluated the incidence of clinical fractures by self-administered questionnaire every year and confirmed them by medical records. We also collected information about daily walking time and weekly exercise time, general health status, body composition including bone mineral density, lean body mass, fat mass and laboratory data at baseline. We compared the frequency of the incidence of clinical fractures in RA patients and Cont for seven years and analyzed risk factors for clinical fractures in RA patients using multivariate regression analysis. Results: A total of 208 patients with RA (mean age: 54.9 ± 10.1 years, female: 85.1%, mean disease duration 14.0 ± 11.8 years) and 205 Cont (mean age: 56.3 ± 10.4 years, female: 83.9%) were finally analyzed. The number of clinical fractures were no differences between RA and Cont group (RA: 47, Cont: 38, p=0.37). Comparing RA patients with or without the clinical fractures, age (p=0.006), disease duration (p=0.005), the average glucocorticoid dose (p<0.001), the average number of falls (p<0.001), and the average DAS28-ESR of seven years (p=0.029) were higher in patients with the incidence of clinical fractures. Multivariate logistic regression analysis revealed that RA was not a risk factor (OR: 0.655, 95%CI: 0.296 – 1.448, p=0.296), and the lack of exercise habit (OR: 2.221, 95%CI: 1.208-4.082, p=0.001) and glucocorticoid use (OR: 2.279, 95%CI: 1.036-5.015, p=0.04) were the risk factor for clinical fractures. Multivariate logistic regression analysis in RA patients, the lack of exercise habit represented an independent risk factor for the incidence of clinical fractures (OR: 4.466, 95%CI: 1.212-16.454, p=0.025). Conclusion: Seven years of data from the TOMORROW cohort study including both RA patients and age- and sex-matched Cont showed no difference in the incidence rate of clinical fractures between RA and Cont groups. Multivariate logistic regression analysis revealed that RA was not a risk factor. However, the lack of exercise habit was significantly associated with an increased frequency of the incidence of clinical fracture among RA patients. Acknowledgement: We wish to thank Atsuko Kamiyama, Tomoko Nakatsuka and the members of the Osaka City University hospital clinical research center. Disclosure of Interests: Shohei Anno: None declared, Kentaro Inui Speakers bureau: Takeda Pharmaceutical, Pfizer Japan, Daiichi-Sankyo Co.Ltd., Abbvie, Mitsubishi Tanabe Pharma Corporation, Janssen Pharmaceutical, Chugai Pharmaceutical, Ono Pharmaceutical, Eisai Co.Ltd., Eli-Lilly, Nippon Kayaku Co., Ltd., Maruho Co., Ltd, Kaken Pharmaceutical Co., Ltd., Yuko Sugioka: None declared, Kenji Mamoto: None declared, Tadashi Okano Speakers bureau: AbbVie, Masahiro Tada Speakers bureau: Abbvie, Astellas Pharma, Bristol-Myers Squibb, Chugai Pharmaceutical, Eisai, Janssen Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Ono Pharmaceutical, Pfizer Japan, Takeda Pharmaceutical, Tatsuya Koike Speakers bureau: AbbVie, Astellas Pharma Inc., Bristol-Myers Squibb, Chugai Pharmaceutical, Eisai, Janssen, Lilly, Mitsubishi Tanabe Pharma Corporation, MSD, Ono Pharmaceutical, Pfizer, Roche, Takeda Pharmaceutical, Teijin Pharma, and UCB, Hiroaki Nakamura: None declared